RETRACTED: Predictive modelling of post-monsoon groundwater quality in Telangana using machine learning techniques - Olentsova Julia; Kukartsev Vladislav; Orlov Vasiliy; Semenova Evgenia; Pinchuk Ivan (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001